Factors Affecting the Investment Climate, SMEs Productivity and Entrepreneurship in Nigeria - Odafe Martin Egere, Juliana Amarachi Anigbo, Paul Agu Igwe, Amarachi Ngozi Amaugo Oyedele M. Ogundana (European Journal of Sustainable Development, 2018)
In Nigeria, most of businesses operate in the form of Small and Medium Enterprises (SMEs). SMEs play a significant role in the economic development of many nations. This paper employs current perspectives to examine the factors affecting investment, productivity and growth of SMEs by employing the World Bank Enterprise Survey in Nigeria. It explored five main factors affecting investment and productivity in Nigeria as follows: education of the labour force, access to infrastructure, access to finance, size of firms and other business climate variables. Other business climate variables are insecurity, bribe or corruption, the amount of time that businesses spend dealing with government regulation, poor power availability, etc. In a survey of 2,676 firms, access to finance (33.1%), access to electricity (27.2%) and the level of corruption (12.7%) were the most ranked obstacles for business owners. By employing the World Bank Enterprise Survey, this paper presents and analyses the business environment challenges at the national level. Keywords: SMEs, Enterprise, Productivity, Sustainability and African Business Environment.